Debt Financing and profitability of listed companies in the Colombo stock exchange of Sri Lanka - Kasthury, S.; Subramaniam, V.A.; Anandasayanan, S. (University of Peradeniya, 2019)
The capital structure decision plays a significant role in firm’s profitability and is crucial for any organization. Capital structure is the composition of capital that an organization uses for financing its overall operations and growth. It is the combination of debt and equity capital that the firm uses for investing and operating activities. A business can seek for different level of mixtures of equity and debt or other financial facilities with equity having the emphasis on maximizing the firm’s value. Also, it affects the liquidity and profitability of a firm. Therefore, it is important to take a proper care and attention in determining the capital structure of a firm. An optimal capital structure is usually defined as one that will minimizing firm’s cost of capital, while maximizing the firm value. Many studies have been undertaken on the capital structure since Modigliani and millers (1958) landmarked. Among them, the effect of capital structure on firm’s profitability has received a considerable attention in the finance literature. According to Modigliani and millers’ (1958) irrelevance theory, in a perfect capital market, the capital structure is unrelated to the firm’s market value, which will be settled by the composition of its assets. Also they found that the firm’s value depends on its operating profitability rather than is capital structure under perfect capital market assumptions.